2021
DOI: 10.1021/acsenergylett.1c00009
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency All-Polymer Solar Cells with Poly-Small-Molecule Acceptors Having π-Extended Units with Broad Near-IR Absorption

Abstract: We report two new poly-small-molecule acceptors, PYN-BDT and PYN-BDTF, which serve, by virtue of their π-extended naphthalene rings, as broad optical cross-section macromolecular absorbers (extending to ∼900 nm; ΔE opticalgap = 1.38 eV) in all-polymer solar cells (APSCs). APSCs fabricated by blending PYN-BDT or PYN-BDTF with PM6 exhibit power conversion efficiencies (PCEs) of 7.24 and 9.08%, respectively, while blends with PBDB-T exhibits far higher PCEs of 12.06 and 13.22%, respectively; the latter cell achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 56 publications
0
58
0
Order By: Relevance
“…It is well known that the relatively low J sc (normally <25 mA cm À2 ) and large E loss (>0.55 eV) are the prominent factors that restrict the current PCE of all-PSCs compared to the record-high SMAs-based PSCs, which have the impressive J sc s (~29 mA cm À2 ). 35,36 Therefore, further effort will be required to boost the desired light absorption in the near-infrared (NIR) region to enhance J sc in all-PSCs. Therefore, several molecular design strategies are analyzed as follows to provide insights for the future development of PSMAs: (a) Core fused-ring optimization.…”
Section: Design Of Psmasmentioning
confidence: 99%
“…It is well known that the relatively low J sc (normally <25 mA cm À2 ) and large E loss (>0.55 eV) are the prominent factors that restrict the current PCE of all-PSCs compared to the record-high SMAs-based PSCs, which have the impressive J sc s (~29 mA cm À2 ). 35,36 Therefore, further effort will be required to boost the desired light absorption in the near-infrared (NIR) region to enhance J sc in all-PSCs. Therefore, several molecular design strategies are analyzed as follows to provide insights for the future development of PSMAs: (a) Core fused-ring optimization.…”
Section: Design Of Psmasmentioning
confidence: 99%
“…Very recently, the PCEs of all‐PSCs have been increased up to over 14% mainly via the optimization of FREA structures (Figure S1 and Table S1, Supporting Information). [ 22–26 ]…”
Section: Introductionmentioning
confidence: 99%
“…In comparison of the synthetic steps and costs of nearly 50 photovoltaic materials reported in literatures (Figure 1), it could be found that the synthesis steps of the high‐efficiency polymer materials except PTQ10 are as high as 15 steps or more (such as for PTzBI‐dF [ 29 ] and PYN‐BDTF [ 30 ] ), and the cost calculation [ 23 ] shows that the combined cost even exceeds ¥1000 per gram. In comparison with the polymer donors, the synthesis steps of most small‐molecule donors are less (about 10 steps), and the synthesis cost is lower (within ¥600 per gram).…”
Section: Introductionmentioning
confidence: 99%